SOCIAL PARTICIPATION IN OLDER ADULTS WITH AND WITHOUT KNEE OSTEOARTHRITIS OVER 1-YEAR. (11th November 2018) - Herbolsheimer, F; Peter, R; Deeg, D; ,
Abstract: Objective. There is little evidence on personal and social consequences of osteoarthritis (OA) as most studies in the field focused on impairment, functional disability, general health status or quality of life. This study addresses the personal and social consequences of osteoarthritis by comparing older adults with and without knee OA across six European countries. Methods. Longitudinal data from the European Project on OSteoArthritis (EPOSA) from 2011 and 2012 were used. 2, 283 participants from six European countries (Germany, Italy, the Netherlands, Spain, Sweden, and the United Kingdom) participated in both waves. Diversity and frequency of social participation was assessed using the Maastricht Social Participation Profile. Frequency and duration of walking, cycling, and sports activities were assessed with the LASA Physical Activity Questionnaire. Mean differences in social participation between both waves were examined using multivariable regression models. Results. At baseline, older adults with knee OA participated less in social activities compared to older adults without OA (M=5.2 vs. M=5.8; p=.003). Changes in social participation did not significantly differ between participants with knee and without knee OA over one year. However, remaining physically active between both measurement points served as a stronger predictor for keeping up social participation in older adults with knee OA compared to those without knee OA (β=.04; p=.039). Conclusion. Knee OA has social consequences which might have been underestimated in the past. The results highlight the relevance of physical activity for maintaining social participation especially among older adults with knee OA.